2015
DOI: 10.1063/1.4933124
|View full text |Cite
|
Sign up to set email alerts
|

Performance change of few layer black phosphorus transistors in ambient

Abstract: Transistors were fabricated based on mechanical exfoliated few layer black phosphorus (BP) flakes, and performance change of these devices exposed to air was explored systematically. BP devices were found to suffer severe performance degradation in ambient conditions, and the field effect mobility drops to less than 1/10 of the original in no more than 120 hours after fabrication. However the current on/off ratio shows completely different time dependent behavior to the published result, i.e. increases with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Since the first report on field-effect transitions in 2014, 2D layered black phosphorus (BP) has emerged as a rising star in electronic, , optoelectronic, photocatalytic, and photovoltaic applications due to its excellent electronic and optical properties that include layer-dependent band gap of 0.3 to 2.0 eV, high charge-carrier mobility, and large current on/off ratios . In particular, the easily tunable band gap enables BP to be available to harvest sunlight from ultraviolet to near-infrared in the solar spectrum .…”
mentioning
confidence: 99%
“…Since the first report on field-effect transitions in 2014, 2D layered black phosphorus (BP) has emerged as a rising star in electronic, , optoelectronic, photocatalytic, and photovoltaic applications due to its excellent electronic and optical properties that include layer-dependent band gap of 0.3 to 2.0 eV, high charge-carrier mobility, and large current on/off ratios . In particular, the easily tunable band gap enables BP to be available to harvest sunlight from ultraviolet to near-infrared in the solar spectrum .…”
mentioning
confidence: 99%
“…It is typical for BP to completely deteriorate within 5 days, where the BP flake will disintegrate physically/visually over time, and its degradation in electrical performance will manifest as a reduction in current. [13,29,42,43] This demonstrates that by creating this hybrid of BP with an organic PDPPSe-TVT polymer semiconductor, we have not only successfully demonstrated enhancement of optoelectronic properties of photodetection and current-voltage transfer characteristics of transistors, but polymer also serves as a passivation layer to prevent highly sensitive BP from the degradation at ambient conditions. Such organic and inorganic material combination provides a great opportunity to understand the synergic effect and optoelectronic light management of two distinct class of materials.…”
Section: Resultsmentioning
confidence: 78%
“…Thus, taking into account the strong interrelation of the electronic parameters of the phosphorene with its adsorption and catalytic properties, it becomes clear that all of the above makes it difficult to manufacture phosphorene-based sensors with reproducible parameters. But the main disadvantage of black phosphorus, limiting its use in humidity sensors, is still the instability of their parameters [ 29 , 31 , 33 , 59 , 134 ]. It was found that if bulk BP was stable at atmospheric conditions for a few months, then exfoliated 2D BP showed a relatively high reactivity and strong air instability [ 135 ].…”
Section: Bp-based Humidity Sensorsmentioning
confidence: 99%